2006
DOI: 10.1002/ccd.20858
|View full text |Cite
|
Sign up to set email alerts
|

Origin and distribution anomalies of the left anterior descending artery in 70,850 adult patients: Multicenter data collection

Abstract: Our series is the biggest series where relatively sufficient clinical and angiographic information about the LAD anomalies were provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 25 publications
4
112
0
3
Order By: Relevance
“…In a retrospective analysis of Tuncer et al [21] with 70,850 patients, its incidence was 0.014%. In this analysis, they reported 2 patients with type L-I, 1 patient with type L-II, 1 patient with type R-I, 3 patients with type R-II and 3 patients with type R-III [21]. In the analysis of Yamanaka et al [23] with 126,595 patients, the incidence of SCA was found to be 0.045%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a retrospective analysis of Tuncer et al [21] with 70,850 patients, its incidence was 0.014%. In this analysis, they reported 2 patients with type L-I, 1 patient with type L-II, 1 patient with type R-I, 3 patients with type R-II and 3 patients with type R-III [21]. In the analysis of Yamanaka et al [23] with 126,595 patients, the incidence of SCA was found to be 0.045%.…”
Section: Discussionmentioning
confidence: 95%
“…SCA constitutes 2-4% of all coronary anomalies and its incidence in population is 0.014-0.066% [6,10,21]. In a retrospective analysis of Tuncer et al [21] with 70,850 patients, its incidence was 0.014%.…”
Section: Discussionmentioning
confidence: 98%
“…In the absence of atherosclerotic stenosis, ischemia can be a result of anatomical malformations, including an acute takeoff angle of the anomalous vessel, myocardial squeezing, vasospasm and a small artery. 1 In these cases, double RCAs were identified as isolated coronary anomalies. Two previous studies have reported double RCA in combination with other anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these were reported to be anomalies of origin or distribution, with separate ostia of the left anterior descending artery and left circumflex artery being the most common. 1 Although many of the primary congenital coronary anomalies are hemodynamically insignificant, it is important to know the anatomic variants in patients with coronary artery disease who are undergoing either surgical myocardial revascularization or coronary angioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…If any anatomical pattern observed in >1% of an unselected population is considered as normal or variant of normal, then an anomalous origin of the coronary arteries is not exceptional. Indeed, the angiographic prevalence is around 0.5% in a cohort pooling several studies published since 1990 (Angelini et al, 1999, Aydinlar et al, 2005, Cieslinski et al, 1993, Garg et al, 2000, Kardos et al, 1997, Ouali et al, 2009, Rigatelli et al, 2003, Tuncer et al, 2006, Yamanaka et al, 1990 and with the possibility to individualise clearly the following ANOCOR: anomalous connection with the opposite sinus or non-coronary sinus, anomalous connection with the contralateral coronary artery, single coronary artery, and anomalous connection with the pulmonary artery. The latter was excluded in one study (Ouali, 2009).…”
Section: Prevalencementioning
confidence: 95%